(Na0.5K0.5)NbO3 nanocrystalline powders produced by high energy ball milling and corresponding ceramics. (June 2017) - Jiten, Chongtham; Rawat, Mahima; Bhattacharya, Angana; Singh, K. Chandramani
Graphical abstract: Highlights: (Na0.5 K0.5 )NbO3 nanopowders prepared by high-energy ball milling at various speeds. Electrical, ferroelectric, piezoelectric properties of resulting ceramics studied. High d 33 (114 pC/N) achieved against (80 pC/N) reported in literature. The increased properties attributed to changed crystal structure and microstructure. Abstract: High-energy ball mill was used for producing (Na0.5 K0.5 )NbO3 nanopowders by milling at 100, 175, 250, 325 and 400 rpm, each for 20 h. Increasing milling speed from 100 to 400 rpm results in gradual reduction in particle size from 90 nm till it finally saturates out at about 5 nm. The microstructural, dielectric, ferroelectric and piezoelectric properties of the corresponding ceramics exhibit strong dependence on the size of the initial nanocrystalline powders. As milling speed increases from 100 to 325 rpm, crystallite size, dielectric constant ( ɛ RT ), remnant polarization ( P r ), piezoelectric charge coefficient ( d 33 ) and electromechanical coupling factor ( k p ) increase from 32.55 to 147.52 nm, 580 to 792, 2.07 to 10.05 μC/cm 2, 83 to 114 pC/N, and 0.28 to 0.43, respectively. Further increase to 400 rpm leads to reversing the trends of change in these parameters. The optimum values of d 33 (114 pC/N) and k p (0.43) were obtained, significantly higher than the maximum value (80 pC/N) reported for conventionally sintered KNN ceramics.